Adverse selection and health insurance decisions of young migrant workers: An empirical study in China - Wang, Hongbo; Gong, Xi (Frontiers in Public Health, 2023)
During the urbanization process of China, adverse selection is becoming a more serious challenge to health insurance, especially towards young migrant workers. This study aims to analyze the adverse selection of young migrant workers in China from two mobility dimensions: mobility distance and settlement intention. Using data from China Migrants Dynamic Survey (CMDS) in 2017, this study analyzed the adverse selection through three problems: First, whether young migrant workers participate in health insurance. Second, which type of health insurance they prefer to choose. Third, how these choices are affected by mobility distance and settlement intention. The results show that there are serious “adverse selection” phenomena towards young migrant workers when deciding whether to participate in health insurance or choose a type of health insurance, that is, healthy individuals tend not to participate in health insurance or not to participate in Urban Employee Basic Medical Insurance (UEBMI) type with higher payment level. The increase of mobility distance can reduce the probability of young migrant workers participating in health insurance, but it could increase the possibility of choosing UEBMI. The enhancement of settlement intention can not only increase the possibility of young migrant workers participating in insurance but also increase their choosing for UEBMI.